Kalai-smorodinsky bargaining solution for the logone river basin water allocation - Maya, Ernest (African Scientific Journal, 2023)
This paper focuses on methods to resolve the ongoing conflict between users in the logone Basin, over water sharing. It addresses the problem by using the cooperative negotiations games framework. It identifies difficulties of choosing the most suitable solution to the Nash bargaining problem under independence of irrelevant alternatives that may obstruct negotiations on water allocation. A positive mathematical programming is applied to find the net agricultural benefit of the players involved in the competition about water management. In the second time the Kalai‑Smorodinsky solution is recommended as optimal in the concrete situation because it considers efficiency of water use of the involved users and its sequential use leads to a Pareto‑optimal outcome.